In silico investigation of lysostaphin-producing novel strains as an enzybiotic against methicillin-resistant Staphylococcus aureus. (2021) - Hossein Mohammadzadeh Hosseini Moghri, Seyed Amir; Hassan Kiadeh, Saeed Ghanbari; Rahaiee, Somayeh
Abstract: The methicillin-resistant Staphylococcus aureus (MRSA) strain has attracted much attention as a health-threatening pathogen and there is an urgent need for finding new drugs. In the present study, an in silico approach was utilized to investigate lysostaphin as a novel enzybiotic against MRSA strains. The protein sequences of the seven selected strains capable of producing lysostaphin were analyzed using several standard bio-computational tools such as CYS_REC, ProtParam, CFSSP, I-TASSER, Algpred, VaxiJen, MEGA-X. Database searching in order to effect identification of disulfide bonds in lysostaphin from novel strains was also performed using the CYS_REC tool. Disulfide bonds play a key role in the thermal stability and targeted interaction of proteins. The results showed that the instability index and the aliphatic index of proteins are 23.52–38.30 and 52.29–90.44, respectively indicating their thermostable nature. The extinction coefficient was achieved from 36120 to 97205 M −1 cm −1 . The studied proteins had GRAVY indexes ranging from −0.027 to −0.955 indicating the possibility of being globular (hydrophilic) proteins. Finally, our findings suggest that the APA99638.1, AYC37596.1, AZG45378.1, TVY73715 and RYC72466 novel sequences of lysostaphin-producing strains can be used as novel therapeutic agents against MRSA strains.